2008
DOI: 10.1021/es703007n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enrichment with Salicylate on Bacterial Selection and PAH Mineralization in a Microbial Community from a Bioreactor Treating Contaminated Soil

Abstract: We investigated enrichment with salicylate as a method to stimulate the degradation of polycyclic aromatic hydrocarbons (PAHs) by a microbial communityfrom a bioreactortreating PAH-contaminated soil. DNA-based stable isotope probing (SIP) was used to compare the effect of alternate methods of salicylate addition (spike vs slow, continuous addition) on the diversity of the enriched microbial community. After identification of salicylate degraders by SIP, real-time quantitative PCR (qPCR) primers were developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…The bacteria capable of degrading BaP (Burkholderiales) in B and BS treatments were detected as identical using DNA-SIP (see Table S1 in the supplemental material). Nevertheless, the similar BaP removal efficiency between the B and BS treatments hinted that BaP degradation was not stimulated by the functional microbial structure change and increasing Burkholderiales-related bacteria, consistent with a previous study by Powell (38). Since small pH variation might significantly affect the biodegradation of xenobiotics and other organic compounds in oligotrophic environments (55), the possible reason was the decreased PAH degradation activity of dominant Burkholderialesrelated bacteria under low-pH conditions (56), like the pH of 6.0 in Mt.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The bacteria capable of degrading BaP (Burkholderiales) in B and BS treatments were detected as identical using DNA-SIP (see Table S1 in the supplemental material). Nevertheless, the similar BaP removal efficiency between the B and BS treatments hinted that BaP degradation was not stimulated by the functional microbial structure change and increasing Burkholderiales-related bacteria, consistent with a previous study by Powell (38). Since small pH variation might significantly affect the biodegradation of xenobiotics and other organic compounds in oligotrophic environments (55), the possible reason was the decreased PAH degradation activity of dominant Burkholderialesrelated bacteria under low-pH conditions (56), like the pH of 6.0 in Mt.…”
Section: Discussionsupporting
confidence: 91%
“…DNA-SIP has been widely applied to the identification of pollutant degraders in numerous environmental media and with an ever-expanding pool of compounds (22,27,38). In the present study, the coupling of DNA-SIP and TRFLP techniques revealed the bacteria correlated with BaP metabolism in soils from Mt.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations